1994
DOI: 10.1002/fam.810180306
|View full text |Cite
|
Sign up to set email alerts
|

Fire conditions for smoke toxicity measurement

Abstract: This paper identifies those fire conditions most often present when smoke toxicity is the cause of death. It begins with a review of the evidence that smoke-inhalation deaths are in the majority in fire fatalities in the United States. Next, there is an analysis of the evidence from the national fire experience showing the connection between post-flashover fires and smoke-inhalation deaths. Third is a presentation of real-scale fire test results demonstrating that postflashover conditions are necessary to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 13 publications
(1 reference statement)
2
61
0
2
Order By: Relevance
“…Hirschler showed that materials with low HRR also possess low smoke emission [114]. Although examples of typical fire histories demonstrate that fire deaths are primarily caused by toxic gases, the toxicity of the vast majority of common construction materials is similar [115]. Thus, the relative toxicity of combustion gases plays a smaller role than the HRR of a fire.…”
Section: Cone Calorimeter Test Methods Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirschler showed that materials with low HRR also possess low smoke emission [114]. Although examples of typical fire histories demonstrate that fire deaths are primarily caused by toxic gases, the toxicity of the vast majority of common construction materials is similar [115]. Thus, the relative toxicity of combustion gases plays a smaller role than the HRR of a fire.…”
Section: Cone Calorimeter Test Methods Evaluationmentioning
confidence: 99%
“…HRR is the key indicator of real-scale fire performance of a material or construction, including ignition, flammability [71], and smoke emission generation [115] is the only test method that attempts to replicate end-use conditions.…”
Section: Comparison Of Small-scale Test Datamentioning
confidence: 99%
“…Las pinturas intumescentes, como único sistema pasivo posible, reaccionan a los incrementos térmicos superiores a los 200º C aproximadamente. El análisis prestacional determina que el colapso de las cerchas de cubierta se puede llegar a producir para unas temperaturas de la estructura inferiores al valor de reacción del producto químico, por lo tura adiabática en una superficie sólida es aquella para la cual el flujo de calor neto es nulo [3].…”
Section: Escenario De Incendiounclassified
“…Furthermore, the generation of carbon monoxide (CO), the most common toxicant, can vary by orders of magnitudes, depending on the fire conditions. 10 An analysis of the U.S. fire fatality data 11 showed that postflashover fires comprise the leading scenarios for life loss from smoke inhalation. Thus, it is most important to obtain data regarding the generation of harmful species under postflashover (or otherwise underventilated) combustion conditions.…”
Section: Introductionmentioning
confidence: 99%